The impact of a change in work posture on work-related musculoskeletal disorders among sewing-machine operators, managed within a physiotherapy and ergonomics programme - Mostert-Wentzel, Karien (University of Pretoria, 2013)
Dissertation (MPhysT)--University of Pretoria, 2013.